Cutaneous manifestations of mixed connective tissue disease: Study from a tertiary care hospital in Eastern India - Sumit Sen; Pradyot Sinhamahapatra; Supriyo Choudhury; Anusree Gangopadhyay; Sanchaita Bala; Geetabali Sircar; Gobinda Chatterjee; Alakendu Ghosh (Wolters Kluwer Medknow Publications, 2014)
Context: Mixed connective tissue disorder is an uncommon disease. Some scientists are reluctant to recognize it as a separate entity. Some others have defined this ailment. Cutaneous features of this condition are unique. Researchers from India have described these features to relate to those described in the studies from other parts of the globe. Aims: This study aims to delineate the skin manifestations of clearly defined mixed connective tissue disease (MCTD) patients, to compare them with those established as overlap syndrome, and to relate them with studies from other parts of the globe. Settings and Design: Successive patients who fulfilled the specific criteria for MCTD presenting in the skin outpatient department of a tertiary care hospital in eastern India were clinically examined from 2009 for 3 years. Materials and Methods: The number of participants was 23 and the dermatological features of these were compared with 22 patients with overlap syndrome. The antibody to uridine-rich U1 ribonucleoprotein was measured for all patients. Statistical Analysis Used: SPSS (Version 17) and MedCalc (Version 11.6). Results: The Male: Female ratio among the MCTD patients was 1:6.67 and that of the overlap syndrome was 1:10. Twenty patients of the MCTD group presented with synovitis as against only seven in the overlap group. Raynaud's phenomenon was present in some of the subjects. Puffy fingers were rare in our study. Facial numbness was reported by four of those suffering from MCTD. Antinuclear antibody (ANA) was essentially of a speckled pattern in this disease Conclusions: Cutaneous indicators of MCTD are distinct from overlap syndrome. Knowledge of these manifestations prevalent in a region may lead to early diagnosis of the disease.